Gynaecological causes of acute abdominal pain. Issue 2 (February 2021) - Stickland, Alice E.J.; Phillips, Christian
Abstract: Acute abdominal pain is common and accounts for 5–10% of all emergency department admissions. The extensive nature of the differentials can make the definitive diagnosis challenging, particularly in women of childbearing age. There is often a conundrum as to whether the emergency is of gynaecological or surgical origin: delay in diagnosis can result in significant morbidity and mortality. This article explores the history, examination and investigation of women presenting with acute abdominal pain. It considers common gynaecological causes, including those found in pregnancy.